2012
DOI: 10.4204/eptcs.93.2
|View full text |Cite
|
Sign up to set email alerts
|

Bisimulation of Labeled State-to-Function Transition Systems of Stochastic Process Languages

Abstract: Labeled state-to-function transition systems, FuTS for short, admit multiple transition schemes from states to functions of finite support over general semirings. As such they constitute a convenient modeling instrument to deal with stochastic process languages. In this paper, the notion of bisimulation induced by a FuTS is addressed from a coalgebraic point of view. A correspondence result is proven stating that FuTS-bisimulation coincides with the behavioral equivalence of the associated functor. As generic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…As a consequence of the general result relating FuTS bisimulation and behavioral equivalence we obtain, in a systematic way, a coalgebraic underpinning of all quantitative bisimulations discussed.with non-determinism as well as with discrete probability distributions over behaviours-and for their comparison with other recent approaches to a uniform treatment of SPC semantics, e.g. Rated Transition Systems [19], Rate Transition Systems [10], Weighted Transition Systems [18], and ULTraS [6].In [24] we proposed a coalgebraic view of FuTS involving functors FS(·, R ), for R a semiring, in place to deal with quantities. Here, for a set of states S, we use FS(S, R ) to denote the set of all finitely supported functions from S to R. Discrete probability distributions are a typical example of such a function space.…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…As a consequence of the general result relating FuTS bisimulation and behavioral equivalence we obtain, in a systematic way, a coalgebraic underpinning of all quantitative bisimulations discussed.with non-determinism as well as with discrete probability distributions over behaviours-and for their comparison with other recent approaches to a uniform treatment of SPC semantics, e.g. Rated Transition Systems [19], Rate Transition Systems [10], Weighted Transition Systems [18], and ULTraS [6].In [24] we proposed a coalgebraic view of FuTS involving functors FS(·, R ), for R a semiring, in place to deal with quantities. Here, for a set of states S, we use FS(S, R ) to denote the set of all finitely supported functions from S to R. Discrete probability distributions are a typical example of such a function space.…”
mentioning
confidence: 86%
“…Note, this excludes by no means the treatment of non-deterministic systems. Below and in [11,24] it has been shown that the class of FuTS given by the definition above is sufficiently rich to deal with all the major stochastic process description languages and their underlying semantic models.…”
Section: Definitionmentioning
confidence: 99%
See 1 more Smart Citation
“…The correspondence result shown in [Latella et al 2012] sets the basis for a systematic study of SPCs, within the FuTS framework, based on category theory, and in particular within the coalgebraic framework, similar to what has been done for probabilistic models in [Bartels 2002;Bartels et al 2003;Sokolova and de Vink 2004], for Rated TSs by Klin and Sassone [2008] and WTSs [Klin 2009]. We think this is a promising line of future research which should be undertaken for FuTSs; in particular, the relationship between WTSs Weighted GSOS on one hand and FuTSs and related PCs sematics rules on the other seems an interesting line of research.…”
Section: Discussionmentioning
confidence: 99%
“…In [Latella et al 2012] the notion of bisimulation induced by FuTSs is addressed from a co-algebraic perspective. A correspondence result is proven stating that FuTS-bisimulation coincides with the behavioral equivalence of the associated functor.…”
Section: · 33mentioning
confidence: 99%